Investigação dos constituintes químicos não voláteis do chá das folhas de Plectranthus ornatus Codd e avaliação do seu potencial terapêutico sobre o modelo animal zebrafish (Danio rerio) - Agostinho, Joana Deyse Lima (2024)
Tea is one of the most consumed beverages in the world, with the market valued at US$ 127.3 billion in 2023. Several plants are used to prepare this drink, many of which have already proven therapeutic uses. However, some Plectranthus species commonly used for medicinal purposes still do not have scientific pharmacological studies, such as Plectranthus ornatus Codd, known as boldinho or boldo-gambá, used in the form of tea to treat gastrointestinal and liver diseases. In this context, the present study aimed to investigate the non-volatile chemical constituents of tea obtained by decoction of fresh P. ornatus leaves collected at Professor Francisco José de Abreu Matos Medicinal Plant Garden at UFC and further evaluate their therapeutic potential in zebrafish (Danio rerio) animal model. Thus, the chloroform and n-butyl soluble fractions, obtained from the liquid-liquid partition of the lyophilized tea were subjected to successive chromatographic fractionations, including Sephadex LH-20, SPE cartridge, and HPLC leading in the isolation of six compounds: five diterpenes: (11R)-acetoxy-2-oxo-neoclerode-3,13E-dien-15-oic acid (DPO-13), ornatin H (DPO-14), ornatin I (DPO-15), ornatin J (DPO-16 ), and ornatin C (DPO-17), and a polyphenol: rosmarinic acid (DPO-1). The designated compounds DPO-14, DPO-15, and DPO-16 are reported for the first time. The structure determinations were performed by spectroscopic analysis (IR, 1H and 13C NMR, and HRMS) and comparison with literature data. In the pharmacological assays, six samples were tested: the lyophilized teas from the initial study (DPO-A, 2017) and the current study (DPO-B, 2022) and the compounds DPO-1, DPO-3, DPO-11, and DPO-13. All compounds were isolated in the first study (2017), but only DPO-1 and DPO-13 were isolated in the present study. Toxicity, nociception, and inflammation assays were performed in a zebrafish (D. rerio) animal model. None of the samples exhibited acute toxicity at the doses tested (4, 20, and 40 mg/kg). In the nociception assays, all samples showed antinociceptive activity in at least one of the doses tested, with the best results for DPO-B and DPO-3, which exhibited activity at the lowest dose (4 mg/kg). In the assay to evaluate the neuromodulation of the nociceptive effect, only the lyophilized tea samples, DPO-A and DPO-B, showed a mechanism of action via the TRPA1 receptor. Regarding the acute inflammation assays, only DPO-11 (4, 20, and 40 mg/kg) and DPO-13 (20 and 40 mg/kg) exhibited anti-inflammatory activity, with the best results for DPO-11, which showed activity from the lowest dose (4 mg/kg). Thus, the results support the main documented ethnopharmacological uses for P. ornatus, since gastrointestinal and liver diseases are conditions that cause pain and inflammation. These results open new perspectives for research involving Plectranthus teas, including the possibility of giving back to society, especially for those seeking support from Professor Francisco José de Abreu Matos Medicinal Plant Garden at UFC.